Предмет: Алгебра,
автор: medvedevsaveli
помогите
упростите выражение
(к-3)(к+3)-(2+к) в квадрате
и найдите его значение при к= -2,5
Ответы
Автор ответа:
0
k^2 - 9 - (k^2 + 4k + 4) =
= k^2 - 9 - k^2 - 4k - 4 =
= - 4k - 13
k = - 2,5
4*2,5 - 13 = - 3
= k^2 - 9 - k^2 - 4k - 4 =
= - 4k - 13
k = - 2,5
4*2,5 - 13 = - 3
Похожие вопросы
Предмет: Математика,
автор: nikysa33
Предмет: Английский язык,
автор: jaroslavaserduk
Предмет: Геометрия,
автор: Min2323
Предмет: Математика,
автор: jh8kmxx
Предмет: Информатика,
автор: Defend3r